A perspective of the epidemiology of malaria and anaemia and their impact on maternal and perinatal outcomes in Sudan - Ishag Adam; Elhassan M Elhassan; Abd Elrahium D Haggaz; Abdel Aziem A Ali; Gamal K Adam (Journal of Infection in Developing Countries)
Introduction: Both malaria and anaemia have adverse effects on maternal and perinatal outcomes. Thus there is an urgent need to investigate the co-epidemiology of malaria and anaemia and their combined impact on maternal and perinatal outcomes in the different regions of Sudan